Membangun Budaya Literasi Melalui Berkisah - Hibana, Hibana (ACIECE, 2018)
The purpose of this study is to find out how the strategy of building literacy culture throughstorytelling. The method which is used in this study is descriptive qualitative, namely libraryresearch. This method was conducted using some steps, in purpose to collect data andinformation from various reading sources in the form of books and material in the library. Thisstudy used a qualitative approach, using an analytical descriptive analysis. The results of thisstudy indicated that 1) literacy ability was the key someone’s success, because it would opentheir scientific horizons, 2) literacy culture must be built since early childhood, because it wouldaffect the children personality throughout their ages, 3) stories or story telling had veryimportant role in the building of children's mentality and the building a literacy culture. 4) Thestrategy of building a literacy culture through storytelling, conducted in several ways: Choosethe story which suited with the child's situation and condition, and read it. Involve diverseemotions and intonations in reading stories. Give motivation to children to read on their own sothat the children could read independently. Provide a variety of reading books. Motivatechildren to read on their own. Listen to the children when they read a book, don't forget to givea positive appreciation. Give the children motivation to tell about the reading contents.Appreciate the slightest achievement which could be achieved by the children